Theoretical Approaches for Modeling the Effect of the Electrode Potential in the SERS Vibrational Wavenumbers of Pyridine Adsorbed on a Charged Silver Surface - Aranda, Daniel; Valdivia, Samuel; Soto, Juan; López-Tocón, Isabel; Avila, Francisco J.; Otero, Juan C. (Frontiers in Chemistry, 2019)
Vibrational wavenumbers of pyridine adsorbed on a silver electrode have been correlated to the calculated ones from different theoretical approaches based on DFT methods. The vibrational tuning caused by the electrode potential has been simulated by means of pyridine-silver clusters with different densities of charge or, alternatively, under applied external electric fields. Both methodologies predict correctly a qualitative red-shift of the vibrational wavenumbers at negative potentials. As a result, harmonic frequency calculations performed at the B3LYP/LanL2DZ level of theory by using a linear [AgnPy]q complex model with different densities of charge (qeff=q/n) have exhibited the best agreement with the experimental observations although the tuning amplitudes are overestimated. Electric fields calculations are unable to account for subtle details observed in the spectra related to the differentiated chemical nature of the metal-molecule bond at positive or negative potentials with respect to the potential of zero charge of the electrode.